Extreme environmental events – a proposed classification (based on the example of Central Europe) - Ustrnul, Zbigniew; Niedźwiedź, Tadeusz (Quaestiones Geographicae, 2025)
This paper presents a classification concept for extreme environmental events, particularly emphasising meteorological, hydrological and geomorphological phenomena. The scheme was originally developed during the Polish national research project Extreme Meteorological and Hydrological Events in Poland – Assessment and Forecasting of Their Impacts on the Human Environment (2004–2009). Over the past decade and a half, it has been verified against observed extreme events and the international literature. Although devised primarily for Poland, the typology applies to the wider Central-European region. Events are grouped according to their genetic origin. Capital letters denote the five principal categories identifying the immediate physical cause: M – meteorological, H – hydrological, G – geomorphological, O – oceanographical and X – other (including complex or poorly defined) environmental events. Within each category, types and subtypes are distinguished. The framework also allows the combination of two or more categories or types and can be further expanded or modified in the future.